2012
DOI: 10.1002/etc.1894
|View full text |Cite
|
Sign up to set email alerts
|

Adult tree swallow survival on the polychlorinated biphenyl–contaminated Hudson River, New York, USA, between 2006 and 2010

Abstract: The upper Hudson River basin in east central New York, USA, is highly contaminated, primarily with polychlorinated biphenyls (PCBs). Reduced adult survival has been documented in tree swallows (Tachycineta bicolor) at a similarly PCB-contaminated river system in western Massachusetts. The purpose of the present study was to assess whether adult survival of tree swallows was likewise affected in the Hudson River basin. Between 2006 and 2010, a total of 521 female tree swallows were banded, of which 148 were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Survival rates of swallows are related to spring weather conditions, as suggested from reports of high mortality of adults during periods of inclement weather (Dence 1946, Weatherhead et al 1985, Custer et al 2012) and our precipitation results for Saskatchewan ( Fig. 5).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Survival rates of swallows are related to spring weather conditions, as suggested from reports of high mortality of adults during periods of inclement weather (Dence 1946, Weatherhead et al 1985, Custer et al 2012) and our precipitation results for Saskatchewan ( Fig. 5).…”
Section: Discussionsupporting
confidence: 77%
“…5). Custer et al (2012) estimated survival of adult female tree swallows, and suggested that poor spring weather caused low female survival (0.29) in one of four years (range = 0.29-0.54). Low apparent survival observed at Mud Creek, Ontario, in 2002 and2007 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of hepatic cytochrome P450A (CYP1A) in avian species by dioxin-like PCBs with comparable structural and biochemical properties to dioxins may lead to embryo lethality and toxic side effects (Kennedy et al, 1996;Manning et al, 2013). Reduced nest provisioning behavior and decreased chick survival were observed in European starlings and tree swallows (Tachycineta bicolor) from PCB-contaminated sites in southern Illinois (Arenal et al, 2004) and the Hudson River, New York, USA (Custer et al, 2012). Population declines in several bird species have been reported in Europe and North America due to bioaccumulation of DDTs, especially DDE (Douthwaite and Tingle, 1992;Ludwig, 1996).…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Birds have been successfully used as sentinel species to monitor the levels and effects of POPs in the environment because they are widespread, sensitive to environmental changes, and often high on the food chain (Dauwe et al, 2006;Van den Steen et al, 2010a,2010bCuster et al, 2012;Sun et al, 2012;Eng et al, 2014). Predatory birds have been widely used as biomonitoring species for POPs (Chen et al, 2009b;Chen and Hale, 2010;Eulaers et al, 2011;Gómez-Ramírez et al, 2014), but most of these birds are less suitable to reflect the local contamination status because they are migratory and live in an extended area with low population densities (Dauwe et al, 2006(Dauwe et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%